Recommendations for the use of tolvaptan in autosomal dominant polycystic kidney disease: a position statement on behalf of the ERA-EDTA Working Groups on Inherited Kidney Disorders and European Renal Best Practice - Gansevoort, Ron T.; Arici, Mustafa; Benzing, Thomas; Birn, Henrik; Capasso, Giovambattista; Covic, Adrian; Devuyst, Olivier; Drechsler, Christiane; Eckardt, Kai-Uwe; Emma, Francesco; Knebelmann, Bertrand; Le Meur, Yannick; et al. (Nephrology, dialysis, transplantation, 2016)
Abstract. Recently, the European Medicines Agency approved the use of the vasopressin V2 receptor antagonist tolvaptan to slow the progression of cyst developm